Antidepressant Effects of Resveratrol in an Animal Model of Depression - Akinfiresoye, Laura L. Hurley, Luli (2014)
Resveratrol (3,4’,5-trihydroxy-trans-stilbene) is a natural non-flavonoid polyphenol antioxidant extracted from red grapes in the processing of wine. Initially it was studied for its potential as anticancer drug, and later was found to reduce cardiovascular disease. More recently resveratrol was shown to alleviate depressive-like symptoms induced by stress or other means in mice and rats. The major purpose of this study was to investigate whether resveratrol would manifest an antidepressant effect in Wistar-Kyoto (WKY) rats, a putative and non-induced animal model of depression, and whether this effect might be associated with an increase in hippocampal and frontal cortical brain-derived neurotrophic factor (BDNF), a protein implicated in chronic effects of many antidepressants. Adult male WKY rats were injected with two doses of resveratrol (10 and 40 mg/kg, i.p.) and their behavior in the open field locomotor activity (LMA), forced swim test (FST: a measure of helplessness), and sucrose preference test (SPT: a measure of anhedonia) was evaluated after a single acute injection or following 7 days of daily treatment. Both acute and chronic administration of resveratrol resulted in a dose-dependent decrease in FST. However, only chronic resveratrol resulted in dose-dependent increase in sucrose consumption. LMA was not affected by any treatment. Parallel to the observed behavioral effects the level of hippocampal, but not frontal cortical, BDNF was also dose-dependently elevated after chronic resveratrol administration. These findings indicate an antidepressant-like effect of resveratrol in an animal model of depression possibly via activation of hippocampal BDNF, and suggest therapeutic potential of resveratrol in at least a subpopulation of depressed patients.